Beta-1,2-linked oligomannosides from Candida albicans act as signals for tumor necrosis factor alpha production. - Jouault, T (1995)
Different cell wall components from Candida albicans have been shown to stimulate murine macrophages for tumor necrosis factor alpha (TNF-alpha) secretion. All of these molecules contain beta-1,2-oligomannosides. In order to examine their role in TNF-alpha production, acid-labile oligosaccharides, released from C. albicans VW32 cell wall phosphopeptidomannan by mild acid hydrolysis, and previously shown to correspond to homopolymers of beta-1,2-linked mannopyranosyl units, were separated by gel filtration chromatography according to their degree of polymerization. Murine macrophages incubated with purified oligomannosides (M2 to M8) released TNF-alpha to an extent which was dependent on, although not directly correlated with, the length of the mannosyl chain. Slight activity was observed with M4 and M5; M6 and M7 had virtually no effect, whereas M8 was associated with strong TNF-alpha release. This effect of M8 was dose dependent and was not altered by polymyxin B, known to interfere with lipopolysaccharide-induced TNF-alpha production. These results suggest that stimulation of TNF-alpha release by C. albicans glycoconjugates containing beta-1,2-linked oligomannosides may be due, at least in part, to the presence of these components.